The interrelationship between records management and big data in Malaysian organization: challenges, opportunities, and future directions/ Nor Sakila Asnawi, Irwan Kamaruddin Abd Kadir and Alwi Mohd Yunus - Asnawi, Nor Sakila; Abd Kadir, Irwan Kamaruddin; Mohd Yunus, Alwi (Faculty of Information Management, 2025)
Big data has changed how organizations handle information, but it also brings challenges that need better management. This paper emphasizes that effective records management is crucial for making the most of big data. By providing clear guidelines for managing data, records management ensures data is accurate, reliable, and accessible, which helps in gaining valuable insights. Records management helps with organizing and preserving large amounts of data, covering everything from creation to storage. It also ensures compliance with regulations, reducing risks of data breaches and legal issues. The paper discusses how integrating strong records management practices into big data strategies can improve data quality and decision-making. Well-organized records make it easier to handle big data and use it effectively. By reviewing current research and real-world examples, the paper shows how records management is key to getting the best results from big data. It offers recommendations for combining records management with big data efforts to improve data governance, security, and usefulness.